Labrundinia pilosella Loew - Saether, Ole A. (Zenodo, 2011)
Labrundinia pilosella (Loew) (Fig. 6 C, D) Material examined. CANADA: Manitoba, Lake Winnipeg, Beaver Creek, 1 male, 28.vii. 1971. The hypopygium of the Lake Winnipeg specimen (Fig. 6 D) differs slightly from that illustrated by Roback (1971 fig. 543). The cibarial pump, tentorium and stipes are shown in Fig. 6 C. Distribution and ecology. The species is known from all over North America, and from Mexico, Puerto Rico, Trinidad and Venezuela (Roback 1971: 277; Oliver et al. 1990: 12; Spies 1999; Epler 2003, 2010; Caldwell 2009; Ashe & O’Connor 2009: 166). Lammers (1975: 3143) found the species in the wetland adjacent to Beckman Lake, Minn., while Roback (1987: 204) found the larvae between willow roots in Savannah River, Georgia. The Lake Winnipeg specimen is from an emergence trap in a small bay with scanty vegetation. Published as part of Saether, Ole A., 2011, Notes on some tanypods from Lake Winnipeg, Manitoba, Canada (Diptera: Chironomidae), pp. 26-42 in Zootaxa 3069 on page 40, DOI: 10.5281/zenodo.201708